Central Venous Pressure and Clinical Outcomes During Left-Sided Mechanical Support for Acute Myocardial Infarction and Cardiogenic Shock - Whitehead, Evan H.; Thayer, Katherine L.; Burkhoff, Daniel; Uriel, Nir; Ohman, E. Magnus; O'Neill, William; Kapur, Navin K. (Frontiers in Cardiovascular Medicine, 2020)
Background: Right ventricular failure (RVF) is associated with increased mortality among patients receiving left ventricular mechanical circulatory support (LV-MCS) for cardiogenic shock and requires prompt recognition and management. Increased central venous pressure (CVP) is an indicator of potential RVF. Objectives: We studied whether elevated CVP during LV-MCS for acute myocardial infarction complicated by cardiogenic shock is associated with higher mortality. Methods: Between January 2014 and June 2019, we analyzed hemodynamic parameters during Impella LV-MCS from 28 centers in the United States participating in the global, prospective catheter-based ventricular assist device (cVAD) study. A total of 132 patients with a documented CVP measurement while on Impella left-sided support for cardiogenic shock were identified. Results: CVP was significantly higher among patients who died in the hospital (14.0 vs 11.7 mmHg, p=0.014), and a CVP >12 identified patients at significantly higher risk for in-hospital mortality (65% vs 45%, p=0.02). CVP remained significantly associated with in-hospital mortality even after adjustment in a multivariable model (adjusted OR 1.10 [95% CI 1.02-1.19] per 1 mmHg increase). LV-MCS suction events were non-significantly more frequent among patients with high versus low CVP (62.11 vs 7.14 events, p=0.067). Conclusion: CVP is a single, readily accessible hemodynamic parameter which predicts a higher rate of short-term mortality and may identify subclinical RVF in patients receiving LV-MCS for cardiogenic shock.